Nicotine modulates the long-lasting storage of fear memory - Lima, Ramón H. (2013)
Late post-training activation of the ventral tegmental area (VTA)–hippocampus dopaminergic loop controls the entry of information into long-term memory (LTM). Nicotinic acetylcholine receptors (nAChR) modulate VTA function, but their involvement in LTM storage is unknown. Using pharmacological and behavioral tools, we found that α7-nAChR-mediated cholinergic interactions between the pedunculopontine tegmental nucleus and the medial prefrontal cortex modulate the duration of fear-motivated memories, maybe by regulating the activation state of VTA–hippocampus dopamine connections.